How non-designers understand the architecture design project: a comparative study using immersive virtual reality - Serpa, F. (2020)
This study focusses on how people who are not familiar with the traditional methods used to represent architecture understand architecture design projects. The main objective of the study was to assess the client's level of comprehension of a design project presented using traditional representation methods in comparison with a method based on the use of immersive virtual reality. Two experiments were conducted, involving architects, design projects and real clients. In both experiments an architecture design project was presented using two different methods: i) the traditional method, ii) the immersive method, using virtual reality, viewed by means of a Head Mounted Display. The results were used to address the questions posed during the study regarding comprehension of architecture design projects. They confirmed the hypothesis that individuals who are not familiar with architectural representations have a better and more accurate perception of a project after viewing it using immersive virtual reality rather than looking at technical drawings, renders and scale models.